The tasks of public administration in waste management in Poland - Jabłoński, Maciej (Studia Ecologiae et Bioethicae, 2011)
The act on waste defines the rule of conduct with waste into the way protecting the life and the health of people and the environmental protection according to the principle of the sustainable development, in particular, the principle of prevention for coming into existence of waste or limiting the quantity of waste and their negative environmental impact, as well as the recycling or neutralizing of waste.